Phenotyping placental oxygenation in Lgals1 deficient mice using 19F MRI - Philipp Boehm-Sturm (Nature Portfolio, 2021)
Abstract Placental hypoperfusion and hypoxia are key drivers in complications during fetal development such as fetal growth restriction and preeclampsia. In order to study the mechanisms of disease in mouse models, the development of quantitative biomarkers of placental hypoxia is a prerequisite. The goal of this exploratory study was to establish a technique to noninvasively characterize placental partial pressure of oxygen (PO2) in vivo in the Lgals1 (lectin, galactoside-binding, soluble, 1) deficient mouse model of preeclampsia using fluorine magnetic resonance imaging. We hypothesized a decrease in placental oxygenation in knockout mice. Wildtype and knockout animals received fluorescently labeled perfluoro-5-crown-15-ether nanoemulsion i.v. on day E14-15 during pregnancy. Placental PO2 was assessed via calibrated 19F MRI saturation recovery T1 mapping. A gas challenge with varying levels of oxygen in breathing air (30%, 60% and 100% O2) was used to validate that changes in oxygenation can be detected in freely breathing, anesthetized animals. At the end of the experiment, fluorophore-coupled lectin was injected i.v. to label the vasculature for histology. Differences in PO2 between breathing conditions and genotype were statistically analyzed with linear mixed-effects modeling. As expected, a significant increase in PO2 with increasing oxygen in breathing air was found. PO2 in Lgals1 knockout animals was decreased but this effect was only present at 30% oxygen in breathing air, not at 60% and 100%. Histological examinations showed crossing of the perfluorocarbon nanoemulsion to the fetal blood pool but the dominating contribution of 19F MR signal is estimated at > 70% from maternal plasma based on volume fraction measurements of previous studies. These results show for the first time that 19F MRI can characterize oxygenation in mouse models of placental malfunction.